2020
DOI: 10.3390/cancers13010040
|View full text |Cite
|
Sign up to set email alerts
|

The m6A RNA Demethylase ALKBH5 Promotes Radioresistance and Invasion Capability of Glioma Stem Cells

Abstract: Recurrence of GBM is thought to be due to GBMSCs, which are particularly chemo-radioresistant and characterized by a high capacity to invade normal brain. Evidence is emerging that modulation of m6A RNA methylation plays an important role in tumor progression. However, the impact of this mRNA modification in GBM is poorly studied. We used patient-derived GBMSCs to demonstrate that high expression of the RNA demethylase, ALKBH5, increases radioresistance by regulating homologous recombination (HR). In cells dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 67 publications
1
54
1
Order By: Relevance
“…Further, ALKBH5 was found to suppress progression in pancreatic cancer and hepatocellular carcinoma [30,31]. Moreover, ALKBH5 was also suggested to increase glioma stem cell radioresistance by regulating homologous recombination [32]. Meanwhile, Li et al identified ALKBH5 to enhance treatment response to anti-PD-1 therapy in melanoma, colorectal, and potentially other cancers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Further, ALKBH5 was found to suppress progression in pancreatic cancer and hepatocellular carcinoma [30,31]. Moreover, ALKBH5 was also suggested to increase glioma stem cell radioresistance by regulating homologous recombination [32]. Meanwhile, Li et al identified ALKBH5 to enhance treatment response to anti-PD-1 therapy in melanoma, colorectal, and potentially other cancers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nine mammalian homologues have been identified, ALKBH1-8 and the fat mass and obesity associated protein (FTO), with each displaying unique roles in genomic stability ( Fedeles et al, 2015 ). ALKBH5 and FTO are the most well characterized of the AlkB homologs and their silencing or deletion reduces the expression of a number of HR and other repair genes in glioblastoma stem cells ( Kowalski-Chauvel et al, 2020 ) and osteoblasts ( Zhang et al, 2019 ), increasing their susceptibility to genotoxic damage. Interestingly, ALKBH2 and ALKBH3 have been shown biochemically to act as DNA repair enzymes that oxidize 5mC to generate 5hmC, 5fC, and 5caC, similarly to TET enzymes ( Bian et al, 2019 ).…”
Section: Potential Roles For Vitamin C In Genomic Stability Via Modulation Of Additional α-Kgddsmentioning
confidence: 99%
“…et al, 2020 ). The m 6 A-demethylase ALKBH5 has been shown to be overexpressed in patient-derived glioblastoma stem cells and may influence radio-resistance via regulation of DNA damage response genes including Chk1 ( Kowalski-Chauvel et al, 2020 ).…”
Section: A In Brain Disordersmentioning
confidence: 99%